Evaluating the Impact of Learning Management System Usage on Student Satisfaction and Learning Outcomes at Universitas Islam Negeri (UIN) Maulana Malik Ibrahim During the COVID-19 Pandemic - Karim Amrullah, Abdul Malik; Bayramov, Shahin; Aziz, Abdul; Haris, Abd. (MyResearch ID Publishing, 2024)
Purpose – This study explores the impact of Learning Management System (LMS) usage on the online learning experience at Universitas Islam Negeri (UIN) Maulana Malik Ibrahim Malang, Indonesia during the COVID-19 pandemic. It aims to evaluate student satisfaction and identify challenges faced during this transition, contributing to the broader discussion on optimizing LMS for enhancing student outcomes and satisfaction in higher education, particularly in times of crisis. Methods/Design/Approach – A quantitative descriptive approach was employed, with data collected from 400 respondents through online surveys using Likert-scale questions. The sample included students and faculty members involved in online learning. The study used statistical analysis to assess satisfaction levels and identify key challenges in LMS adoption, particularly focusing on the use of the MOODLE platform. Findings – The use of MOODLE LMS increased from 18.5% in the first semester of the pandemic to 51% in the second semester, reflecting greater platform acceptance. Students reported moderate satisfaction with an overall score of 3.8 out of 5. Challenges included limited internet access (63.5%), insufficient internet quota subsidies (63.3%), and low satisfaction with academic services (2.73) and online learning policy promotion (2.76). Originality/Value – This study provides insights into LMS adoption in a specific educational and cultural context, highlighting both the potential and the challenges of digital learning platforms during a global crisis. It offers practical recommendations for improving LMS design and implementation in higher education. Practical Implications – The findings suggest universities should enhance digital infrastructure and offer financial support to overcome technical barriers such as limited internet access. Improving academic services and promoting clearer online learning policies will further increase LMS effectiveness and student satisfaction. Keywords LMS, MOODLE, student satisfaction, online learning, COVID-19 pandemic. Paper type Research paper